The Karate Kid collection - Macchio, Ralph, 1961-; Morita, Pat, 1932-2005; Swank, Hilary; Avildsen, John G., 1935-2017; Cain, Christopher, 1943-; Kamen, Robert Mark; Lee, Mark; Columbia Pictures; Jerry Weintraub Productions; Sony Pictures Home Entertainment (Firm) (2005)
A rousing series of four uplifting, coming-of-age adventures that will leave you cheering. Two teenagers learn important lessons in life, friendship and the art of self-defense from their wise mentor, Mr. Miyagi.
Disc 1. The Karate Kid (1984 ; 126 min.) / Columbia Pictures ; a Jerry Weintraub production ; written by Robert Mark Kamen ; produced by Jerry Weintraub ; directed by John G. Avildsen -- Disc 2. The Karate Kid II (1986 ; 113 min.) / Columbia Pictures ; a Jerry Weintraub production ; produced by Jerry Weintraub ; directed by John G. Avildsen ; written by Robert Mark Kamen -- Disc 3, side A. The Karate Kid Part III (1989 ; 112 min.) / Columbia Pictures ; a Jerry Weintraub production ; produced by Jerry Weintraub ; written by Robert Mark Kamen ; directed by John G. Avildsen -- Disc 3, side B. The next Karate Kid (1994 ; 104 min.) / Columbia Pictures ; a Jerry Weintraub production ; produced by Jerry Weintraub ; written by Mark Lee ; directed by Christopher Cain.
Title from container.
Originally produced as individual motion pictures in 1984-1994.
Special features: Commentary with director John Avildsen, writer Robert Kamen, actors Ralph Maccio, Pat Morita ; "The way of the Karate kid: part 1 and part 2" featurette ; "Beyond the form" featurette ; "East meets West: a composer's notebook" featurette ; "Life of Bonsai" featurette ; original promotional featurette ; filmographies ; trailers.
Karate kid: Director of photography, James Crabe ; edited by Bud Smith, Walt Mulconery, John G. Avildsen ; music by Bill Conti ; production designed by William J. Cassidy.
Karate kid II: Music by Bill Conti ; director of photography, James Crabe ; edited by John G. Avildsen, David Garfield, Jane Kurson ; costume designer, Mary Malin.
Karate kid III: Music by Bill Conti ; director of photography, Stephen Yaconelli ; edited by John G. Avildsen, John Carter ; production designed by William F. Matthews.
Keywords: Karate -- California -- Los Angeles -- Drama; Karate -- Training -- Drama; Teenagers -- Conduct of life -- Drama; Bullying -- Drama; Karate -- Drama; Sports tournaments -- Drama; Martial artists -- Drama; Martial arts schools -- Drama; Revenge -- Drama; Feature films; Martial arts films; Coming-of-age films; Fiction films; Video recordings for the hearing impaired